2018
DOI: 10.1111/1759-7714.12788
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an eight‐week outpatient‐based pulmonary rehabilitation program for advanced lung cancer patients undergoing cytotoxic chemotherapy in Korea

Abstract: The scientific evidence supporting pulmonary rehabilitation (PR) for lung cancer patients undergoing cytotoxic chemotherapy is accumulating; however, the feasibility of outpatient‐based PR in these patients has not yet been evaluated in Korea. We conducted an eight‐week outpatient‐based PR feasibility study in a tertiary referral hospital setting. Patients with advanced lung cancer (non‐small cell lung cancer IIIB–IV and small‐cell lung cancer extensive disease) scheduled to undergo first‐line cytotoxic chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…Previous studies that reported the effects of PR in patients with lung cancer focused mostly on perioperative periods [10-17,23], whereas only a few studies assessed patients with advanced lung cancer [19,21,24,27,30]. In this study, we analyzed the effect of PR on both early- and advanced-stage lung cancer patients, and found improvements in exercise capacity (6MWD) and dyspnea, consistent with previous studies that reported improvements in exercise capacity [10-13,16,21,24,27] or dyspnea grade [21,27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that reported the effects of PR in patients with lung cancer focused mostly on perioperative periods [10-17,23], whereas only a few studies assessed patients with advanced lung cancer [19,21,24,27,30]. In this study, we analyzed the effect of PR on both early- and advanced-stage lung cancer patients, and found improvements in exercise capacity (6MWD) and dyspnea, consistent with previous studies that reported improvements in exercise capacity [10-13,16,21,24,27] or dyspnea grade [21,27].…”
Section: Discussionmentioning
confidence: 99%
“…The factors contributing to poor adherence in previous studies included transportation problems, lack of motivation, work‐related reasons, hospitalization, aggravation of underlying disease, and very low exercise capacity 21,24,25 . One feasibility study of an outpatient‐based PR program for patients receiving chemotherapy reported a completion rate of 75%, in which accessibility and unwillingness were the reasons for refusing the PR program 12 . We observed a relatively higher completion rate than those in previous studies.…”
Section: Discussionmentioning
confidence: 47%
“…A review of studies on preoperative exercise training for patients with NSCLC concluded that exercise training before lung surgery improved exercise capacity and forced vital capacity (FVC) 9 . However, there are few reports of PR programs in lung cancer patients treated with chemotherapy or radiation therapy 10–15 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations